Determinants of Gen Z’s adoption of chatbots in online shopping: An empirical investigation - Brijesh Singh; Massand, Ajay (The Scientific Temper, 2024)
Online shopping is in a growth phase in India. Most of the online shopping companies are leaving no stone unturned to attract customers to their websites or apps. The companies are introducing innovative website/app features to engage their prospects and customers. This study is an exploratory study followed by descriptive analysis to find out the preference of Gen Z customers towards the usage of Chatbots. The sample includes 171 Gen Z customers from Bengaluru, India comprising of different backgrounds. Their preferences have been ascertained with the help of a well-structured questionnaire. The study uses judgment sampling. A conceptual framework has been proposed comprising four factors, namely Brand Perception, Service Quality, Personalization and Demographics. Different statistical techniques like frequency tables, Dimension Reduction methods (Principal Component Analysis) and Multiple Linear Regression are used for data analysis. Authors found the factors viz Brand Percpetion, Service Quality and Personalization to be significant in the varying levels of their importance. The output of the analysis is interpreted and its implications on online shopping companies have been highlighted.